Defy : the power of no in a world that demands yes - Sah, Sunita (Professor) (One World, an imprint of Random House, 2025)
"Why is it so hard to speak up, even when we know something's wrong? This is the definitive book on defiance, a clear-eyed dissection of the forces that silence us, featuring groundbreaking research and legendary stories alongside everyday examples and strategies for how to unleash the power of a "True No.""--